The Influence Of Organizational Culture, Leadership, and Organizational Commitment On Workplace Deviant Behavior Through Job Satisfaction In Government Employees Of The Riau Islands Province - Fanni Okan Perdana; Gita Indrawan; Sri Yanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to determine the direct and indirect effect of organizational culture, leadership, organizational commitment on workplace deviant behavior through job satisfaction in government employees of the Riau Island Province. This type of research uses quantitative research methods with primary and secondary data sources. The population in this study was 109 Civil Servants (PNS) who worked at the Bintan Regency Regional Secretariat office. In this study, data collection was carried out using the census method in which the entire population was taken as a sample. By using the census method, this study aims to obtain accurate and representative data from the entire existing population. This step will make it easier for researchers to analyze and describe the characteristics and events that occur in the population. This research uses Smart-Pls as a data processing tool. The results of this study, Organizational Culture variable (X1) on Job Satisfaction (Z), Leadership variable (X2) on Job Satisfaction (Z), Organizational Commitment variable (X3) on Job Satisfaction (Z), Organizational Culture variable (X1) on Workplace Deviant Behavior (Y1), Leadership variable (X2) on Workplace Deviant Behavior (Y1), Organizational Commitment variable (X3) on Workplace Deviant Behavior (Y1), Job Satisfaction (Z) on Workplace Deviant Behavior (Y1), Job Satisfaction variable (Z) mediates the effect of Organizational Culture (X1) on Workplace Deviant Behavior (Y1), Job Satisfaction variable (Z) mediates the effect of Leadership (X2) on Workplace Deviant Behavior (Y1), Job Satisfaction variable (Z) mediates the effect of Organizational Commitment (X3) on Workplace Deviant Behavior (Y1)